Sustained Release T3 Therapy: Animal Models and Translational Applications - Idrees, Thaer; Price, John D.; Piccariello, Thomas; Bianco, Antonio C. (Frontiers in Endocrinology, 2019)
The standard of care to treat hypothyroidism is daily administration of levo-thyroxine (LT4). This is based on the understanding that deiodinases can restore the production of T3 and compensate for the small amounts of T3 that are normally produced by the thyroid gland. However, pre-clinical and clinical evidence indicating that deiodinases fall short of restoring T3 production is accumulating, opening the possibility that liothyronine (LT3) might have a role in the treatment of some hypothyroid patients. LT3 tablets taken orally result in a substantial peak of circulating T3 that is dissipated during the next next several hours, which is markedly distinct from the relative stability of T3 levels in normal individuals. Thus, the effort to developing new delivery strategies for LT3, including slow release tablets, liquid formulations, use of T3-related/hybrid molecules such as T3 sulfate, poly-zinc-T3, and glucagon-T3, nanoparticles containing T3, the subcutaneous implant of T3-containing matrices, and stem cells for de novo development of the thyroid gland. This article reviews these strategies, their applicability in animal models and translatability to humans.